Complete Regression of Psoriatic Arthritis After Belatacept Conversion in a Highly HLA‐Sensitized Kidney Transplant Patient. Issue 5 (24th January 2017) - Meneghini, M.; Gómez, C.; Mast, R.; Melilli, E.; Grinyó, J. M.; Bestard, O.
Abstract : Costimulatory inhibitors (i.e. abatacept and belatacept) effectively abrogate T lymphocyte activation and proliferation and have been shown to be effective for disease control in certain autoimmune disorders as well as in preventing allograft rejection in kidney transplantation. Whether such immunomodulatory agents may be useful for the control of autoimmune flares and allograft acceptance, while avoiding the need of additional strong immunosuppressants, has not been shown. Here, we report the first case of a 47‐year‐old man affected by a serious debilitating form of psoriatic arthritis that presented during the course of a third, high immunological‐risk kidney transplantation. Three years after transplantation, the patient benefited by switching from tacrolimus‐ to belatacept‐based therapy, without additional immunosuppression, by showing complete regression of the arthritic symptoms as well as no progression of severe radiological lesions, which leaded to the recovery of disability and functional impairment. Remarkably, the treatment with belatacept in association with mycophenolate mofetil and steroids also provided a stable normal allograft function over time and abrogated the development of de novo circulating donor‐specific alloantibodies after 4 years of follow‐up. Abstract : This case report describes the successful clinical and radiological response of a severe form of psoriatic arthritis after belatacept conversion in a highly sensitized kidney transplant patient.